DAMPAK PELAKSANAAN EKSTRAKURIKULER SENI TARI DI SMP NEGERI 20 PADANG - Putri, Adinda; Yuliasma (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
This study aims to describe the impact of dance training implementation on extracurricular activities at SMPN 20 Padang. This type of research is qualitative with a descriptive analytical approach. The main instrument in this study is the researcher themselves, assisted by stationery, a camera and a voice recorder. Data were collected through observation, literature review, interviews and documentation. The steps for analysing the data are data collection, data reduction, data presentation and drawing conclusions. The results of the study indicate that creative dance training at SMPN 20 Padang not only serves as a medium for developing artistic talent but also as a means of character education. In its implementation, the training focused on developing discipline, evident from the increased attendance and engagement of students from one session to the next. This discipline relates not only to punctuality but also encompasses diligence, perseverance, and the attitude of students during activities. The training also integrated group work as a form of cooperative learning, which is beneficial in honing students' social skills, such as communication, teamwork, leadership, and individual responsibility within the group. Although there were challenges in ensuring equal participation among members, the activity remained effective in fostering a sense of togetherness and solidarity. Healthy competition between groups also stimulates student motivation and enhances the quality of the training process.